A Study on the Possibility of Assessing Children’s Development Using an Exercise Workbook Based on the Kumon Method: A Case from the Preparatory Group of Preschool Education (Journal of Interdisciplinary Insights, 2026)
In today’s era of a knowledge-based society and rapid advances in information and communication technology, it is more essential to foster children’s innate curiosity, motivation, and interest in learning than to simply provide them with various forms of knowledge from an early age. Preschool teachers should design developmentally appropriate activities and tasks that correspond to children’s age-specific characteristics, thereby supporting their overall development and enhancing their learning abilities. Teachers must conduct effective assessments by comparing formative (ongoing) and summative (outcome) evaluations of children’s development, ensuring that progress is measured accurately, objectively, and based on reliable evidence.